PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT LANCANG KUNING PEKANBARU - -, Dea Adinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This study aims to determine the influence of the work discipline on the performance of nurses at Rumah Sakit Lancang Kuning Pekanbaru. The population in this study were all nurses who worked at Rumah Sakit Lancang Kuning Pekanbaru as many as 60 people. Sampling uses the census menthod, namely taking the entire population as a research sample. The data analysis used is descriptive analysis, with quantitative analysis tools, namely multiple linear regression with the help of the SPSS program. Based on the test results, it was found that work environment variables and work discipline had a partially positive and significant effect on nurse performance. The results of the F test also show that the work environment and work discipline variabels simultaneously have a positive and significant effect on nurses performance. Keywords : Work Environment, Work Discipline And Nurses Performance.